PENGARUH INFLASI, NILAI TUKAR RUPIAH, DAN SUKU BUNGAN TERHADAP NILAI EKSPOR INDONESIA 2012-2022 - Putri, Amanda Ayudia; Yuvikaria, Arzesy Alena Ayu Yuvikaria; Ainiya, Firda Ainiya (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the fluctuations in Indonesia's export value over the past decade and to understand the macroeconomic factors influencing it, such as inflation, the exchange rate of the Indonesian rupiah, and interest rates. The research employs a quantitative approach using quarterly time series data from 2012 to 2022, along with multiple regression analysis to examine the relationships among the variables. The findings reveal that the exchange rate of the rupiah and interest rates have a significant negative effect on export value, while inflation shows a positive but insignificant influence. The regression model demonstrates strong predictive capability, with an R-squared value of 0.78, indicating that 78% of the variation in export value can be explained by these three independent variables. The results of this study are expected to provide insights for policymakers in formulating effective strategies to enhance Indonesia's export competitiveness and to encourage further research on the economic dynamics affecting the export sector..